ASPEK HUKUM PERLINDUNGAN SAKSI DAN KORBAN PERDAGANGAN ANAK (HUMAN TRAFFICKING) - Siti Nurhayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
Women and child trafficking may occur in any countries. In practice, human trafficking is done in an organized way. The Law No. 12 of 2007 on the Eradication of Human Trafficking (PTPPO) regulate not only individual criminals, but also those carried out by corporations, state officials who abuse their powers, as well as organized groups. Legal breakthrough in this law is the right of victims to not be charged penalties when committing a crime because it is forced by criminal trafficking.